PRODUKSI BIOGAS MENGGUNAKAN CAIRAN ISI RUMEN SAPI DENGAN LIMBAH CAIR TEMPE - Ihsan, Arsul; Bahri, Syaiful; Musafira, Musafira (Natural Science: Journal of Science and Technology, 2013)
This study aimed to determine the effect of ratio of liquid cow contents with tempeh wastewater and fermentation time on biogas production. The research was conducted using a completely randomized design  (CRD) with 7 point ratio variation cows rumen fluid contents with liquid wastewater tempe  (0:100, 5:95, 10:90, 15:85, 20:80, 25:75 and 100:) and fermentation time consisted of 12, 24, 36, 48, 60, 72, 84 and 96 hours. Each treatment was repeated twice. From the results obtained it turns out the highest content of biogas at a ratio of biogas yield of 2894,35 mg/L. Which produces biogas fermentation time the highest yield for 84 hours. Positive test the presence of mhetane in the biogas shown with the blue flame in the flame test.